2020
DOI: 10.3390/jcm9051341
|View full text |Cite
|
Sign up to set email alerts
|

DNA Fragmentation in Viable and Non-Viable Spermatozoa Discriminates Fertile and Subfertile Subjects with Similar Accuracy

Abstract: Sperm DNA fragmentation (sDF) negatively affects reproduction and is traditionally detected in total sperm population including viable and non-viable spermatozoa. Here, we aimed at exploring the ability of DNA fragmentation to discriminate fertile and subfertile men when detected in viable (viable sDF), non-viable (non-viable sDF), and total spermatozoa (total sDF). We revealed sDF in 91 male partners of infertile couples and 71 fertile men (max 1 year from natural conception) with LiveTUNEL coupled to flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Previous studies reported that viable spermatozoa can contain DNA breaks, supporting that apparently intact sperm with proper motility may bear fragmented DNA (Pérez-Llano et al, 2010;Samplaski et al, 2015;Muratori et al, 2020). DNA damage can occur in response to oxidative stress, but also as a result of enzymatic activity during chromatin remodeling and/or apoptotic-like processes (Aitken and De Iuliis, 2010;Sakkas and Alvarez, 2010;Bui et al, 2018;Ribas-Maynou and Benet, 2019).…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies reported that viable spermatozoa can contain DNA breaks, supporting that apparently intact sperm with proper motility may bear fragmented DNA (Pérez-Llano et al, 2010;Samplaski et al, 2015;Muratori et al, 2020). DNA damage can occur in response to oxidative stress, but also as a result of enzymatic activity during chromatin remodeling and/or apoptotic-like processes (Aitken and De Iuliis, 2010;Sakkas and Alvarez, 2010;Bui et al, 2018;Ribas-Maynou and Benet, 2019).…”
Section: Introductionmentioning
confidence: 90%
“…In brief, ten of 12 studies reported that none of the participants had SARS-CoV-2 RNA COVID-19 induces respiratory-predominant multiorgan dysfunction, including myocardial, renal, enteric and hepatic dysfunction, which coincides with the tissue expression of ACE2. 3 Meanwhile, several studies have shown that ACE2 is expressed in human testes (eg spermatogonia, Leydig cells and Sertoli cells), 4,5 suggesting that the testes may be another organ affected by COVID-19.…”
Section: Detection Of Covid-19 In the Male Reproductive Tractmentioning
confidence: 99%
“…In previous research using TUNEL+LD for the simultaneous evaluation of membrane integrity and DNA fragmentation, it was evident that DNA fragmentation was largely associated with dead spermatozoa. 6 Furthermore, using the same method Muratori et al 5 reported that it is possible to discriminate the fertility status of men by evaluating the sperm DNA Fragmentation either in live or dead spermatozoa. This could suggest that the increase of DNA fragmentation is proportional in both fractions, allowing the detection of subfertile patients with the same accuracy when compared to fertile subjects.…”
Section: Detection Of Covid-19 In the Male Reproductive Tractmentioning
confidence: 99%
See 2 more Smart Citations